Governing education without reform: the power of the example. - Simons, Maarten (Discourse: Studies in the Cultural Politics of Education, 2015)
There is an increasing emphasis today on different forms of evidence-based policy in education. Several authors address the related emergence of new patterns of governing and describe forms of governing by numbers and related practices of governing by comparison. There is, however, less focus on the governmental use of soft evidence such as examples of good practice. Drawing on the analysis of governing practices in Belgium (Flanders) and Europe, this article attempts to examine in detail how soft evidence, among other elements, constitutes the current governing configuration. It is argued that this configuration includes several mechanisms that appear as evident but have far-reaching consequences: imposing spaces of meaning and discussion, deciding on what is within one's control and what is not, making people believe there is no longer something beyond themselves that is an excuse for actual self-improvement. What takes shape as part of techniques of contextualization, personalization, and permanent monitoring is ‘the power of the example’: learning from examples in view of increased performance. The conclusion expresses some concerns about the tendencies toward a manipulative society.